2022
DOI: 10.5334/joc.189
|View full text |Cite
|
Sign up to set email alerts
|

Robot’s Social Gaze Affects Conflict Resolution but not Conflict Adaptations

Abstract: Robots are a new category of social agents that, thanks to their embodiment, can be used to train and support cognitive skills such as cognitive control. Several studies showed that cognitive control mechanisms are sensitive to affective states induced by humor, mood, and symbolic feedback such as monetary rewards. In the present study, we investigated whether the social gaze of a humanoid robot can affect cognitive control mechanisms. To this end, in two experiments, we evaluated both the conflict resolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…Gaze cueing effects of robotic gaze have been consistently found with different anthropomorphic robots, including sophisticated ones with eye movement (Kompatsiari et al, 2021;Ciardo and Wykowska, 2022) and those without eye movement (Chaminade and Okka, 2013;Morillo-Mendez et al, 2022. This finding does not automatically categorize such robots as social agents as non-social stimuli such as arrows can also induce automatic gaze cueing effects (Kawai, 2011;Slessor et al, 2016).…”
Section: Robots Gaze Following and The Adoption Of The Intentional St...mentioning
confidence: 98%
“…Gaze cueing effects of robotic gaze have been consistently found with different anthropomorphic robots, including sophisticated ones with eye movement (Kompatsiari et al, 2021;Ciardo and Wykowska, 2022) and those without eye movement (Chaminade and Okka, 2013;Morillo-Mendez et al, 2022. This finding does not automatically categorize such robots as social agents as non-social stimuli such as arrows can also induce automatic gaze cueing effects (Kawai, 2011;Slessor et al, 2016).…”
Section: Robots Gaze Following and The Adoption Of The Intentional St...mentioning
confidence: 98%
“…For example, group identity can alter the neural processing of information during social attention (Kawai, 2011;Kawakami et al, 2014Kawakami et al, , 2017, and learning (Hobson & Inzlicht, 2016). Studies showed that the mere presence of others can influence how people perceive reward and feedback (i.e., social facilitation; Ciardo & Wykowska, 2022;Simon et al, 2014;Zajonc, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Robot verbal feedback has been shown to influence participants' choices (Ham and Midden, 2014). However, robot feedback could also be provided through the non-verbal behavior, like facial expressions, gaze behavior and gestures for instance (Gonsior et al, 2011;Ciardo & Wykowska, 2022;Parenti et al, 2022). Yet, the effects of nonverbal feedback from the robot remain relatively understudied.…”
Section: Introductionmentioning
confidence: 99%